Мовна особистість Тараса Григоровича Шевченка як чинник формування українських філологів - Мацько, Любов; Matsko, Lyubov (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглядається основне поняття лінгвоперсонології: мовна особистість як лінгвістична категорія, що складається з компонентів – мовна спроможність, мовна свідомість і мовнокомунікативна компетентність. Досконалі мовні особистості визначаються як елітарний тип мовних особистостей, що засвідчують максимально високий рівень володіння культурою креативного мовлення і можуть бути зразком для вивчення рідної мови і формування мовнокомунікативної компетентності. Для української молоді безсумнівним чинником патріотичного виховання є мовна особистість національного генія і пророка Тараса Григоровича Шевченка.The article deals with the basic concept of the theory of linguistic personality: linguistic personality as a category consisting of the following components: language ability, language consciousness and communicative competence. Perfect linguistic personalities are defined as an elitist type demonstrating the most advanced level of creative culture and language and serving as a model for the study of the mother tongue and the formation of communicative competence. The study of creative work with such high degree of linguistic creativity by linguistic personalities who were and are emblematic figures, a cultural phenomenon of Ukraine, people who did not only influenced the development of the Ukrainian language and literature, but also enriched the intellectual life of the nation is of especially great informative andeducational value. Linguistic personality of the Ukrainian genius and prophet Taras Shevchenko is a definitive factor for the patriotic education of the Ukrainian youth.
A Linguistic Personality of Taras H. Shevchenko as a Factor for the Formation of Ukrainian Philologists
Keywords: Тарас Шевченко; освіта; патріотизм; мовна особистість; мовна спроможність; мовна свідомість; мовнокомунікативна компетентність; мовленнєві компетенції; Taras Shevchenko; education; patriotism; linguistic personality; language ability; language consciousness; communicative competence; speech competence